The role of the mucin-glycan foraging Ruminococcus gnavus in the communication between the gut and the brain - Erika Coletto; Dimitrios Latousakis; Matthew G. Pontifex; Emmanuelle H. Crost; Laura Vaux; Estella Perez Santamarina; Andrew Goldson; Arlaine Brion; Mohammad K. Hajihosseini; David Vauzour; George M Savva; Nathalie Juge (Gut Microbes)
Ruminococcus gnavus is a prevalent member of the human gut microbiota, which is over-represented in inflammatory bowel disease and neurological disorders. We previously showed that the ability of R. gnavus to forage on mucins is strain-dependent and associated with sialic acid metabolism. Here, we showed that mice monocolonized with R. gnavus ATCC 29149 (Rg-mice) display changes in major sialic acid derivatives in their cecum content, blood, and brain, which is accompanied by a significant decrease in the percentage of sialylated residues in intestinal mucins relative to germ-free (GF) mice. Changes in metabolites associated with brain function such as tryptamine, indolacetate, and trimethylamine N-oxide were also detected in the cecal content of Rg-mice when compared to GF mice. Next, we investigated the effect of R. gnavus monocolonization on hippocampus cell proliferation and behavior. We observed a significant decrease of PSA-NCAM immunoreactive granule cells in the dentate gyrus (DG) of Rg-mice as compared to GF mice and recruitment of phagocytic microglia in the vicinity. Behavioral assessments suggested an improvement of the spatial working memory in Rg-mice but no change in other cognitive functions. These results were also supported by a significant upregulation of genes involved in proliferation and neuroplasticity. Collectively, these data provide first insights into how R. gnavus metabolites may influence brain regulation and function through modulation of granule cell development and synaptic plasticity in the adult hippocampus. This work has implications for further understanding the mechanisms underpinning the role of R. gnavus in neurological disorders.